Pengaruh Lingkungan Kerja, Budaya Organisasi dan Kepemimpinan Transformasional terhadap Kepuasan Kerja Karyawan Millenial - Novia Sulistyawati; Iwan Kresna Setyadi; Jubaedah Nawir (Studi Ilmu Manajemen dan Organisasi, 2022)
Purpose: This research was conducted to determine whether or not the work environment, organizational culture and transformational leadership influence the job satisfaction of millennial generation employees Research methodologi: Sampling of 80 respondents of millennial generation employees in Rw 11 Cakung Timur Cakung, East Jakarta who currently work in a company based on criteria using purposive and roscoe techniques. Analysis technique with path method and analysis tool using SmartPLS 3.3. Results: (1) the work environment has a positive and significant effect on job satisfaction of millennial generation employees in Rw 11 (2) Organizational culture has a positive and significant effect on job satisfaction of millennial employees in Rw 11 (3) Transformational Leadership has a positive and significant effect on job satisfaction of millennial generation employees. Limitations: Technique of distributing questionnaires mostly through g-form considering the current conditions do not allow to be able to deal directly with respondents due to Covid19 and limited references to previous research that examines the same variables and reference object generations millennials are still few. Contribution: Can be a reference for companies in implementing company systems, especially to maintain employee satisfaction.